Development of Local Web-Based Learning (LWBL) as Low-Cost Digital Learning Efforts. (February 2020) - Supratman,; Arianto, Toni; Maiyana, Efmi
Abstract: In a learning practice, we cannot avoidthe use of Information Technology (IT). IT has been able to contribute to the world of education. Learning is more effective, interactive, broad, not time-bound and not patterned only in the classroom. This condition makes IT able to improve the quality of education that can be proud of. The use of IT in the world of education is increasingly being realized its benefits and not only as a complementary medium for educational institutions but has become one of the competitive strategies for institutions in order to improve the quality of its outcomes. In practice, there are some obstacles in the use of IT in learning, namely inadequate infrastructure, inadequate human resources and high operational costs. This research aims to develop a local web-based learning product in an effort to minimize the above constraints. This technology is theoretically able to contribute to students in their learning activities such as increased productivity, flexibility and interactivity without being burdened by the cost of internet access and anxiety in the appearance of content that does not educate when learning takes place. This research uses the 4D version of Research and Development (R&D) approach (Define, Design, Develop, and Disseminate). The results of the study are localhost-based learning websites that can be accessed without the cost of internet access and avoidance of negative content carried by the internet. Based on the test results on the product, it is stated that the products produced can be categorized as valid, effective, and practical to be used in learning.